ENSURING THE EFFICIENCY OF FUEL AND HYDRAULIC UNITS OF AIRCRAFT BY RESTORING WORN PARTS - Мельник, Олексій Валерійович; Якобчук, Олександр Євгенійович (Problems of Friction and Wear, 2021)
Ensuring the efficiency of fuel and hydraulic units of aircraft by restoring worn parts. An analysis of the loss of serviceability of hydraulic units and hydraulic equipment that wear out during the operation of aircraft. The surface physicochemical processes, such as corrosion, erosion is the reason for the largest number of failures of fuel and hydraulic units and hydraulic equipment. When examining the causes of the non-serviceable condition of the investigated components, that the main type of damage is to wear was found, namely: mechano-chemical, fatigue, abrasive, cavitation and fretting corrosion. Each type of wear can be both leading and supplementing. Depending on the operating conditions of the estimated friction pair, its efficiency is defined by the tribomechanical characteristics of the structural materials used for the parts manufacturing of the tribocouple. Cavitation wear is most common in fuel and hydraulic units. It occurs when air cavities slam and cause a water hammer effect. The self-fluxing powder materials are used for plasma spraying and recommended for the restoration of the damaged working surfaces of the parts of the friction units. In this process, intermetallics are part of self-fluxing powder materials. Composite plasma coatings based on iron and nickel significantly increase the incubation period and cavitation resistance compared to the coating without intermetallics. Cavitation destruction of composite coatings reinforced with intermetallics is radically different from the mechanism of destruction of plasma coating based on iron. Mechanisms of wear of composite plasma coatings in the conditions of cavitation wear are established. It is shown that the incubation period of structural materials and coatings correlates with their corrosion resistance. Based on the administered researches, possible directions for the restoration of details of tribocouples of fuel and hydraulic units of aeronautical engineering are developed.